Investing in Hedge Funds when Returns are Predictable - AVRAMOV, Doron (Institutional Knowledge at Singapore Management University, 2007)
This paper evaluates hedge fund performance through portfolio strategies that incorporate predictability in managerial skills, fund risk loadings, and benchmark returns. Incorporating predictability substantially improves performance for the entire universe of hedge funds as well as various subsets based on investment styles. Such out-performance is strongest during market downturns when the marginal utility of consumption is relatively high. Moreover, the major source of investment profitability is predictability in managerial skills. In particular, long-only strategies that incorporate predictable skills outperform their Fung and Hsieh (2004) benchmarks by over 12 percent per year. The economic value of predictability obtains for various rebalancing horizons and is robust to style adjustments as well as adjustments for backfill bias, incubation bias, illiquidity-induced serial correlation, and fees.